Enhancing Critical Thinking in Early Childhood through STEAM-Oriented Busy Board Media: A Development Study - Ningsih, Rahmi Wardah; Farida, Niken (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2023)
This study explores the development and effectiveness of STEAM-based busy board media in enhancing critical thinking skills among children aged 5-6 years. Using the ADDIE model, we created a dual-sided active board integrating science, technology, engineering, arts, and mathematics elements. This research examines the effectiveness of STEAM-based busy board media in improving critical thinking skills in 5-6-year-old children. The study utilized the ADDIE model to create a dual-sided board incorporating science, technology, engineering, arts, and mathematics elements. Conducted in Sidodadi Village kindergartens, the methodology included expert validations, trials, and pretest-posttest evaluations. The initial analysis highlighted the absence of specific media to foster critical thinking in this age group. The busy board was deemed feasible, appropriate, and safe by experts. Significant enhancements in children's critical thinking were observed, with post-test results indicating considerable progress. Statistical analysis using SPSS 22 confirmed the busy board's positive impact, emphasizing STEAM's role in early childhood education. The box panel received high effectiveness ratings in expert assessments (85.3%, 76.1%, 87.1%, and 67.7%). The hypothesis test significantly affected critical call thinking development (0.000 < 0.05). Both expert and user evaluations attested to its effectiveness, with trials showing notable improvements in early childhood critical thinking. However, the study was limited by its geographical focus and lacked long-term impact assessments. These results support the inclusion of sensory tools in early education and call for further investigation into their more comprehensive and action-oriented long-term benefits.